Investigating areas for improvement in the transition from hospital-to-home for frail older adults: A mixed methods study. Issue 6 (December 2022) - Skerry, Leanne; Kervin, Emily; Hanson, Natasha; Jarrett, Pamela; McCloskey, Rose
Background: The planning and execution of discharge plans to successfully transition frail older adults from hospital-to-home can be a complicated endeavour. Objective: To identify areas for improvement in the transitional process of frail older adults who were discharged from hospital based, geriatric units to their homes in the community. Method: A prospective multi-phased mixed methods design was used, and cross-case thematic analysis of Phase 2 data were triangulated with Phase 1 findings. Results: Thematic analysis findings indicated several related areas of importance within the transitional process: 1) Coordination of discharge; 2) Transition-to-home planning; 3) Home and community care; 4) Following of recommendations; and, 5) Medical follow-up. Conclusions: Strengthening communication between stakeholders, as well as the implementation of harmonized policies and guidelines are needed to facilitate more consistent care delivery and provide patients and families with information on what to expect during the transitional process.